Sustained delivery of osteogenic growth peptide through injectable photoinitiated composite hydrogel for osteogenesis - Liu, Beibei; Wu, Jiannan; Sun, Xiaodi; Meng, Qingxun; Zhang, Jian (Frontiers in Bioengineering and Biotechnology, 2023)
One of the most challenging clinical issues continues to be the effective bone regeneration and rebuilding following bone abnormalities. Although osteogenic growth peptide (OGP) has been proven to be effective in promoting osteoblast activity, its clinical application is constrained by abrupt release and easily degradation. We developed a GelMA/HAMA dual network hydrogel loaded with OGP based on a combination of physical chain entanglement and chemical cross-linking effects to produce an efficient long-term sustained release of OGP. The hydrogel polymers were quickly molded under ultraviolet (UV) light and had the suitable physical characteristics, porosity structure and biocompatibility. Significantly, the GelMA/HAMA-OGP hydrogel could promote cell proliferation, adhesion, increase osteogenic-related gene and protein expression in vitro. In conclusion, the OGP sustained-release system based on GelMA/HAMA dual network hydrogel offers a fresh perspective on bone regeneration therapy.